Cardiovascular mortality trends and disparities in U.S. breast cancer patients, 1999–2020: a population-based retrospective study - Yong-Hao Yeo; Boon-Jian San; Jia-Yi Tan; Min-Choon Tan; Teodora Donisan; Justin Z. Lee; Laura M. Franey; Salim S. Hayek (Cardio-Oncology)
Abstract Background Breast cancer survivors face a higher risk of cardiovascular disease (CVD) compared to non-breast cancer patients, yet contemporary data on CVD-related mortality within this group remains scarce. Objective To investigate trends and disparities in CVD mortality among breast cancer patients. Methods We queried the Centers for Disease Control and Prevention’s Wide-Ranging Online Data for Epidemiologic Research (CDC Wonder) and conducted serial cross-sectional analyses on national death certificate data for CVD mortality in breast cancer patients aged 25 and above from 1999 to 2020. We calculated age-adjusted mortality rates (AAMR) per 100,000 individuals and analyzed trends over time using the Joinpoint Regression Program, with further analyses stratified by age, race, census region, and urbanization level. Results A total of 74,733 CVDs with comorbid breast cancer in the United States were identified between 1999 and 2020. The AAMR from CVDs with comorbid breast cancer decreased from 2.57 (95% CI [2.50–2.65]) in 1999 to 1.20 (95% CI [1.15–1.24]) in 2020, with an average annual percent change (AAPC) of − 4.3. The three most common causes of CVDs were ischemic heart disease (47.8%), cerebrovascular disease (17.1%), and hypertensive disease (10.6%). Our analysis revealed a significant decrease in AAMR for all CVD subtypes, except for hypertensive diseases and arrhythmias. The decrease in annual percent change (APC) was more pronounced in individuals aged ≥ 65 years compared to those < 65 years (-4.4, 95%CI [-4.9, -3.9] vs. -2.9, 95%CI [-4.1, -1.7], respectively. Notably, non-Hispanic Blacks consistently exhibited the highest AAMR (1.95, 95%CI [1.90–1.99]), whereas Hispanic or Latina patients had the lowest AAMR (0.75, 95% CI [0.72–0.78]). The AAMR was also higher in rural regions than in urban areas (1.64, 95%CI [1.62–1.67] vs. 1.55, 95%CI [1.53–1.56]). Conclusion The study highlights a significant decline in CVD mortality among breast cancer patients over two decades, with persistent disparities by race and region. Exceptionally, hypertensive diseases and arrhythmias did not follow this declining trend.